Comprehensive FE numerical insight into Finale Emilia Castle behavior under 2012 Emilia Romagna seismic sequence: Damage causes and seismic vulnerability mitigation hypothesis. (15th June 2016) - Tiberti, Simone; Acito, Maurizio; Milani, Gabriele
Highlights: A masonry Castle severely damaged during the 2012 Emilia Romagna (Italy) earthquake is analyzed. A full 3D Finite Element model obtained after a detailed historical/geometrical analysis is used. Modal, Pushover and full non-linear dynamic analyses are conducted for a numerical insight. 3 hypotheses for masonry are done: real situation (partial restoring), no restored and fully restored. FEM confirms the high vulnerability and that a full restoration would have preserved the structure. Abstract: In this paper, a numerical insight on the historical masonry Castle of Finale Emilia, symbol of the consequences occurred after the seismic sequence of 20–29th May 2012 in Emilia Romagna, Italy, is presented. Some different numerical models are critically compared, in order to both have an insight into the causes at the base of the partial collapse of the structure and propose valuable rehabilitation interventions with seismic upgrading to prevent future damage under seismic loads. Two different meshes are utilized, the one very refined and constituted by tetrahedron elements, the other much coarser and mainly constituted by hexahedrons, along with different hypotheses presented for the masonry material (linear and elasto-plastic with damage and softening). The analyses performed include standard modal, nonlinear static (pushover) and nonlinear dynamic analyses, under different hypotheses concerning the material properties of the single walls. Three different configurations are compared, the first is the real one stricken by the earthquake (where only one of the walls had been consolidated), the second is a hypothetical castle without any consolidated wall, the last is the situation that should be encountered after full rehabilitation. At this aim, full three-dimensional (3D) detailed finite element models (FEM) are adopted, starting from the available documentation at disposal (photos and existing drawings). From numerical results, it is found that the insufficient resistance of the constituent materials is mostly responsible for the damages observed and that the partial rehabilitation implemented by the municipality on one wall helped in limiting the damaging effect of the seismic sequence. In all cases, the numerical analyses provide a valuable picture of active damage mechanisms, giving useful hints for the reconstruction and indicating that a limited upgrading of masonry mechanical properties could limit considerably the global seismic vulnerability of the structure, in light of a reconstruction of the collapsed parts of the Castle.